Estimating Seed Quality in Hard Seeded Leguminous Trees by Accelerated Aging and Leachate Conductivity - Singh, Paramjeet; Singh, Ombir; Chandra, Veena (Indian Forester, 1996)
The potential of leachate conductivity and accelerated aging for evaluating seed quality of Gledisia trichanthos and Robinia pseudacacia have been studied and the results are presented in this paper.